Classification of furcation involvement of endodontically treated mandibular first permanent molars based on cone beam CT - TANG Rong; HU Yanni; LIN Zitong (口腔疾病防治, 2023)
Objective To classify the furcation involvement (FI) of endodontically treated mandibular first permanent molars based on cone beam computed tomography (CBCT), provide reference for individualized treatment of FI. Methods CBCT images of the FI of 164 endodontically treated mandibular first permanent molars from 163 patients in Nanjing Stomatological Hospital, Medical School of Nanjing University were collected retrospectively. On the CBCT images, the shape and extent of periapical and periodontitis bone resorption, the thickness of residual dentin in the pulp floor and root canal wall, and the periodontal bone resorption of the complete dentition were evaluated. The FI was classified into periodontal, periapical, perforated and mixed types. Results Among the 164 FIs of endodontically treated mandibular first permanent molars, the periapical type was the most common (41.5%), followed by the mixed type (26.2%), perforated type (18.3%), and periodontal type (14.0%). Among the 68 periapical-type FIs of endodontically treated mandibular first permanent molars, 48.5% were proper root canal filling, 44.1% were insufficient filling and 7.4% were overfilling. Among the 43 mixed-type FIs, the periodontal mixed periapical type was the most common (72.1%). Conclusion Detailed evaluation and classification of furcation involvement could be performed using CBCT images; therefore, the study has guiding significance for clinical treatment.